Proceedings of the 2001 American Control Conference. (Cat. No.01CH37148) 2001
DOI: 10.1109/acc.2001.945966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recursive estimation techniques for position tracking radioactive sources

Abstract: Los Alamos NATIONAL LABORATORY Los Alamos National Laboratory, an affirmative actionlequal opportunityemployer, is operated by the University of California for the U.S. Department of Energy under mntract W-7405-ENG-36. Byaccaptance of this aticle, the publisher recognizes that the U.S. Government retains a nonexclusive, royalty-free license to publish or reproduce the published form of this contribution,or to allow othera to do so, for U.S. Government purposes. Los Alamos National Laboratow requests that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, the algorithm still struggles with highly non-linear processes, as is experienced at lower levels of radiation intensity. As a result, the accuracy of this method is reported to be lower than other methods, particularly MLE algorithms and more complicated RBE filters (GF, EF, and PF) (Brewer 2009;Gunatilaka, Ristic, and Gailis 2007;Morelande, Ristic, and Gunatilaka 2007;Muske and Howse 2001;Towler, Krawiec, and Kochersberger 2012).…”
Section: Rbe Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the algorithm still struggles with highly non-linear processes, as is experienced at lower levels of radiation intensity. As a result, the accuracy of this method is reported to be lower than other methods, particularly MLE algorithms and more complicated RBE filters (GF, EF, and PF) (Brewer 2009;Gunatilaka, Ristic, and Gailis 2007;Morelande, Ristic, and Gunatilaka 2007;Muske and Howse 2001;Towler, Krawiec, and Kochersberger 2012).…”
Section: Rbe Algorithmsmentioning
confidence: 99%
“…Whilst each of the individual algorithms differ in terms of the specific statistical models used or the assumptions made with respect to the initial model conditions (i.e. assumption of a known source radionuclide or intensity), each is based around the Poisson distribution of radioactive decay and emission (Brennan, Mielke, and Torney 2005;Knoll 2010;Muske and Howse 2001;Towler, Krawiec, and Kochersberger 2012). At high radiation intensities, the Poisson distribution equates well to a Gaussian distribution (Brennan, Mielke, and Torney 2005;Towler, Krawiec, and Kochersberger 2012).…”
Section: Algorithms For Radioactive Source Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is tempting simply to attempt to linearize the model in the style of the extended Kalman filter (EKF), but Muske and Howse found that the nature of the nonlinearities inherent in the model can drive at least the EKF unstable [4]. At least part of this instability results from the highly non-Gaussian shape of the Poisson model that describes radioactive sources at low count rates.…”
Section: Prior Work In Radiation Source Localizationmentioning
confidence: 99%